Association of low socioeconomic status with cognitive decline among older persons in underdeveloped areas in China – a data analysis of the Gansu aging study - Juxia Zhang; Yuping Feng; Xiaoli Zhang; Jing wang; Hu Cheng; Yunhua Wang; Jiancheng Wang (BMC Geriatrics)
Abstract Background Individuals with low socioeconomic status (SES) bear a disproportionate share of the cognitive impairment (CI) burden, there are growing evidence focusing on socioeconomic inequalities in CI among older persons. However, data in the underdeveloped regions is limited. This study aims to measure socioeconomic inequalities in CI among individuals aged 65 years or older in Gansu, China, and determine the contributions of socioeconomic factors to the inequalities. Methods Data from the Gansu Aging Study in 2022 including 3241 participants. Participates’ SES was assessed by using education, income, and occupation. Multivariate logistic regression was conducted to identify the associated between SES and CI, and decomposition analysis was further applied to decompose the contribution of each determinant to the observed inequalities in CI. The SES inequalities in CI were illustrated and quantified by the concentration curve index. Results Overall, 24.2% of participants suffered from CI in the study. The likelihood of CI was lower among those with a medium SES (OR = 0.04, 95% CI:0.03, 0.07), good SES (OR = 0.06, 95% CI: 0.04, 0.09) compared to those with lower levels of SES. Older adults with mild depression (OR = 3.66, 95% CI:2.70,4.95), moderate-severe (OR = 2.82, 95% CI:2.05,3.88) were more likely to have CI in comparison to those with no depression and regular social activities were protective factors for CI (OR = 0.28, 95% CI:0.11,0.75). The concentration index indicated that CI was more concentrated in households with poor SES. Subsequently, SES explained 34.65% of socioeconomic inequality in CI. Conclusion This study suggested that, approximately one-quarter of older persons suffered from CI in Gansu, China. Low SES was substantially associated with risk of CI. Although interventions to modify traditional risk factors may decrease the risk of CI, disparities by SES may remain without addressing SES itself.